Disparity of Gut Microbiota Composition Among Elite Athletes and Young Adults With Different Physical Activity Independent of Dietary Status: A Matching Study - Xu, Yongjin; Zhong, Fei; Zheng, Xiaoqian; Lai, Hsin-Yi; Wu, Chunchun; Huang, Cong (Frontiers in Nutrition, 2022)
Objective This study aimed to investigate the disparity of gut microbiota among elite athletes and young adults with different physical activity independent of dietary status. Methods In Hangzhou, China, an age and sex matching study was conducted between April and May 2021. A total of 66 Chinese young adults were recruited in this study and divided into an elite athlete group, physically active group, and physically inactive group. Fecal samples were collected to assess gut microbiota composition. Dietary status was measured using a food-frequency questionnaire. Comparisons in gut microbiota and blood biomarkers among three groups were analyzed by using the analysis of covariance. Results The findings depicted a tendency to form clusters for beta diversity among three groups, while no significant difference was observed in both alpha and beta diversity. In the multiple analysis model, by adjusting dietary status, a significantly higher abundance of Clostridiaceae (p = 0.029) and Megamonas_rupellensis (p = 0.087) was observed in elite athletes compared to that in general young adults. Furthermore, inflammation-related bacteria such as Bilophila (p = 0.011) and Faecalicoccus (p = 0.050) were enriched in physically inactive young adults compared to two other groups. Pearson's correlation analysis showed a positive association between Bilophila and circulating white body cell count (r = 0.332, p = 0.006) and its subtypes including neutrophils (r = 0.273, p = 0.027), and lymphocytes (r = 0.327, p = 0.007). Megamonas_rupellensis has been shown associated positively with serum lymphocytes levels (r = 0.268, p = 0.03). Although no significant differences were observed, the elite athletes tended to have lower levels of blood biomarkers of immunity within a normal range, which may reflect a better immune function. Conclusion This matching study indicated that physically inactive young adults are more likely to have a lower immune function and a higher abundance of pro-inflammatory gut bacteria than elite athletes and physically active young adults. Dietary status should be considered as an important factor that may affect the association of physical activity with immune function and gut microbiota.